Longitudinal Myelopathy in a Child with Systemic Lupus Erythematosus (SLE) – A rare case report and review of the literature - Debnath, Bithi; Mallick, Uzzwal Kumar; Saha, Narayan Chandra (Bangladesh Critical Care Journal, 2021)
Systemic lupus erythematosus (SLE) is a chronic, multisystem autoimmune disease with a highly variable clinical course. Myelopathy is one of the neuropsychiatric lupus syndromes. Although infrequent, it is manifested severely, leading to motor and sensory deficits, and sphincter dysfunction. The exact pathogenesis is still unknown, but may be related to arterial thrombosis and vasculitis. Diagnosis is based on clinical findings, laboratory tests and the use of Magnetic resonance imaging. Here we discuss the clinical presentation, the magnetic resonance imaging findings, and other relevant laboratory studies of this rare but serious complication of systemic lupus erythematosus. Bangladesh Crit Care J September 2021; 9 (2): 112-115